2007
DOI: 10.1021/jp071806p
|View full text |Cite
|
Sign up to set email alerts
|

High Power Battery Electrodes Using Nanoporous V2O5/Carbon Composites

Abstract: Nanoporous composite electrodes for lithium ion batteries were successfully fabricated by coating porous carbon with V 2 O 5 gel, and their high rate capability was demonstrated. The porous carbons prepared by using SiO 2 colloidal crystals as templates exhibited ordered three dimensionally interconnected pores. The porous carbons were immersed in V 2 O 5 sol under reduced pressure repeatedly to obtain V 2 O 5 /carbon composites. The nanoporous V 2 O 5 /carbon composites thus obtained exhibited large capacity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 17 publications
(42 reference statements)
5
64
0
Order By: Relevance
“…That is, a few lithium ions were inserted from LSO into FPO on their contact interfaces and conduct charges in FPO. This is supported by the fact that the observed activation energy of 0.63 eV is close to that for LiFePO 4 , 0.55-0.59 eV. 30 This local reaction between LSO and FPO is not surprising, although LSO is electrochemically stable at this potential of 3.5 V vs. Li/Li + .…”
Section: Sio 3 -Fepomentioning
confidence: 81%
See 1 more Smart Citation
“…That is, a few lithium ions were inserted from LSO into FPO on their contact interfaces and conduct charges in FPO. This is supported by the fact that the observed activation energy of 0.63 eV is close to that for LiFePO 4 , 0.55-0.59 eV. 30 This local reaction between LSO and FPO is not surprising, although LSO is electrochemically stable at this potential of 3.5 V vs. Li/Li + .…”
Section: Sio 3 -Fepomentioning
confidence: 81%
“…5a). 4 nano-composite.-To study composites with higher electrode potential, FePO 4 (FPO) with a potential of 3.5 V vs. Li/Li + was used as an active material, because valence of Ti in TiO 2 is +4 and TiO 2 cannot be further oxidized and higher potential than 3.3 V vs. Li/Li…”
Section: Sio 3 -Litio 2 Nano-composite-to Confirm the Above Modmentioning
confidence: 99%
“…efficient energy consumption and effective usage of renewable energies. Lithium ion batteries (LIBs) and related batteries are supposed to be one of promising energy storage devices [1][2][3][4][5][6]. LIBs used for those purpose would be much larger than conventional LIBs, and all solid state batteries that employ solid electrolytes (especially inorganic ceramics electrolytes) attract interests because of their advantages that are hardly achieved by conventional batteries with liquid organic electrolytes [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Although energy density of LIBs is the largest among present rechargeable devices, their power density is not enough. Their relatively low power density is explained by the following polarizations on the electrode reactions: (1) charge transfer reaction, (2) lithium ion diffusion in solid active materials, (3) electron conduction and (4) electrolyte transport. We have so far proposed and demonstrated that rate capability of lithium ion batteries (LIB) is highly improved by using nano-porous materials (e.g., TiO 2 ,[1,2] V 2 O 5 ,[3] LiFePO 4 ).…”
Section: Introductionmentioning
confidence: 99%